Clinical controversies in the management of acute pulmonary embolism: evaluation of four important but controversial aspects of acute pulmonary embolism management that are still subject of debate and research - Luijten, Dieuwke; Klok, Frederikus A; van Mens, Thijs E; Huisman, Menno V (Expert review of respiratory medicine, 2023)
Acute pulmonary embolism (PE) is a disease with a broad spectrum of clinical presentations. While some patients can be treated at home or may even be left untreated, other patients require an aggressive approach with reperfusion treatment. (1) Advanced reperfusion treatment in hemodynamically stable acute PE patients considered to be at high risk of decompensation and death, (2) the treatment of subsegmental pulmonary embolism, (3) outpatient treatment for hemodynamically stable PE patients with signs of right ventricle (RV) dysfunction, and (4) the optimal approach to identify and treatpost-PE syndrome. Outside clinical trials, hemodynamically stable acute PE patients should not be treated with primary reperfusion therapy. Thrombolysis and/or catheter-directed therapy are only to be considered as rescue treatment. Subsegmental PE can be left untreated in selected low-risk patients, after proximal deep vein thrombosis has been ruled out. Patients with an sPESI or Hestia score of 0 criteria can be treated at home, independent of the presence of RV overload. Finally, health-care providers should be aware of post-PE syndrome and diagnose chronic thromboembolic pulmonary disease (CTEPD) as early as possible. Persistently symptomatic patients without CTEPD benefit from exercise training and cardiopulmonary rehabilitation.